(untitled) - Simchi-Levi, David; Kaminsky, Philip (Boston, 2009)
Includes bibliographical references (p. 483-498) and index; KHQL Quản trị chuỗi cung ứng
Keywords: Physical distribution of goods -- Management; Marketing channels -- Management; Business logistics; Industrial procurement; Phân phối vật chất hàng hóa -- Quản lý; Hậu cần doanh nghiệp